Optimization on Na and Ca bentonite activation using response surface method for increasing selectivity of stevioside in stevia extract - Ayu Rahayu SARASWATI; Erliza NOOR; Titi Candra SUNARTI (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2021)
The demand for stevia extract consumption as an alternative sweetener that contains stevioside with zero-calorie is increasing. However, dark color and high tannin content from stevia leaf extract causes a disturbing aftertaste and reduces interest in consumption. Therefore, the purification process is a mandatory step to be done. Several studies on purification methods show the best approach by adsorption using bentonite. However, natural bentonite has limited adsorption capacity and low selectivity. An activation with acid and high temperature is expected to increase the adsorption capacity of color and its selectivity on maintaining the stevioside at the extract. This study aimed to obtain the optimum acid concentration and temperature for the activation using the Response Surface Method (RSM) experimental design and its application to the purification of stevia leaf extract. Based on the parameter of methylene blue number, the most optimum concentration of H2SO4 used for activation was 0.17 N for both natural bentonite. The heating temperature was 358°C for Na-bentonite and 481°C for Ca bentonite. The maximum adsorption capacities of activated Na and Ca-bentonite were increased from 15.65 and 38.23 mg g-1 to 197.72 and 169.52 mg g-1, respectively. The best adsorbent used for purification is Ca-activated, which increased extract clarification up to 81.37% at 655 nm and 86.64% at 410 nm compared to natural Ca bentonite. It also reduced tannin up to 97.46% and was more selective to recover 50.64% stevia content in the solution, which was higher than other previously reported studies.